Knowledge and Implementation of the Promotion Policies of Elementary Teachers and Administrators in the Division of Misamis Oriental - Uy, Alma O.; Palmes, Nenita D. (JPAIR Multidisciplinary Research, 2009)
The study attempted to determine the knowledge and awareness level of teachers and administrators on promotion policies and extent of implementation of the Implementing Rules and Regulation of Republic Act 9155. There were 424 teachers and administrators who were the respondents of the study, randomly selected from the 24 Districts in the Division of Misamis Oriental. Findings revealed that majority of the teachers and administrators in the Division of Misamis Oriental are aware of the promotion policies. As to comparison of their responses, majority of them like the provision of DepEd Orders No. 42 and 39 s. 2007. Majority of the respondents are also aware on the extent of implementation of Republic Act 9155, its Implementing Rules and Regulations specifically on promotion. There is a significant relationship between the knowledge and awareness level of administrators and teachers on promotion policies and related factors namely: number of trainings and seminars attended educational qualification and the position held by the respondents. There is no significant relationship between the knowledge and awareness level of administrators and teachers on promotion policies with some related variables namely: age, gender, length of service, monthly salary, and performance rating.
Keywords: promotion policies; performance rating; teacher qualifications